2007
DOI: 10.1056/nejmoa063446
|View full text |Cite|
|
Sign up to set email alerts
|

A Communication Strategy and Brochure for Relatives of Patients Dying in the ICU

Abstract: Providing relatives of patients who are dying in the ICU with a brochure on bereavement and using a proactive communication strategy that includes longer conferences and more time for family members to talk may lessen the burden of bereavement. (ClinicalTrials.gov number, NCT00331877.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
840
4
48

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,121 publications
(903 citation statements)
references
References 35 publications
11
840
4
48
Order By: Relevance
“…Among the many potential contributors to these adverse bereavement outcomes are the circumstances surrounding and processes of limiting life support. This hypothesis is supported by evidence that ICU deaths are commonly preceded by decisions to withdraw life support [3], and evidence that both ICU processes of care [4,5] and behaviors of ICU clinicians [1,6] near the end of life can influence family members' post-ICU psychological outcomes. Thus, uncertainty regarding which approaches to withdrawing mechanical ventilation are least distressing for patients and families [7,8] represents an important area for rigorous investigation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Among the many potential contributors to these adverse bereavement outcomes are the circumstances surrounding and processes of limiting life support. This hypothesis is supported by evidence that ICU deaths are commonly preceded by decisions to withdraw life support [3], and evidence that both ICU processes of care [4,5] and behaviors of ICU clinicians [1,6] near the end of life can influence family members' post-ICU psychological outcomes. Thus, uncertainty regarding which approaches to withdrawing mechanical ventilation are least distressing for patients and families [7,8] represents an important area for rigorous investigation.…”
mentioning
confidence: 94%
“…Although several measures have been found to be reliable and valid, responsiveness to ICUbased interventions has been a much more elusive goal. Few studies have found changes in the Impact of Events Scale (IES) [4,5] among family members of critically ill patients, and even fewer have shown responsiveness of the Inventory of Complicated Grief (ICG).…”
mentioning
confidence: 99%
“…While one large trial of an integrative ICU-based palliative care approach studied in 22 French ICUs was associated with significant decreases in family member anxiety, depression, and post-traumatic stress disorder levels [14], only a handful of ICU-based palliative care studies [15][16][17] have measured family-reported outcomes other than ''family satisfaction''. Moreover, ICU-based palliative care trials have thus far not measured truly patient-centered outcomes, such as symptom scores or quality of life [18].…”
mentioning
confidence: 99%
“…Moreover, ICU-based palliative care trials have thus far not measured truly patient-centered outcomes, such as symptom scores or quality of life [18]. Furthermore, other than the previously mentioned French trial [14], all ICU-based palliative care trials have been completed in North America. There is a dearth of adequately powered studies concerning both the impact of ICU-based palliative care on patient-and family-centered outcomes and the delivery of palliative care in non-North American critical care settings.…”
mentioning
confidence: 99%
“…In this sense, many interventions have been tested to improve the quality of EOL care with different results. Ethics and palliative care consultations, intensive communication strategies, formal family conferences combined with the bereavement brochure have been demonstrated to improve the quality of EOL care by reducing the length of stay and the use inappropriate ICU resources, preventing conflicts and reducing psychological burden on family members [8][9][10][11]. Unfortunately, such interventions are still not widely adopted in ICUs [7].…”
mentioning
confidence: 99%